An analysis of factors which contribute to loan delinquency among small and medium enterprises: The case of National Microfinance Bank PLC - Malundila, Farida Msham (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirement for award of the Degree of Masters of Marketing Management of Mzumbe University